ORGANIZATIONAL COMMUNICATION IN INSTITUTIONS: a SYSTEMATIC REVIEW OF LITERATURE - Renovato, Kamila Caixeta Ferreira; Cruz, Iara Martins de Araujo; Fragoso, Virginia de Moura; Nunes, Suzana Gilioli da Costa [UNESP] (Fundacao Univ Tocantins, 2022)
Nowadays, organizations are very concerned about the exchange of information between companies, clients, and employees. The lack or poor positioning of communication impairs various aspects of an organization and consequently institutions do not achieve the desired results. This article proposes an analysis of the relevant contributions of the scientific production on organizational communication from two meetings, EnANPAD and SemeAD, and proposes a dialogue about the role of organizational communication in institutions. The article was developed through a systematic review on organizational communication from the publications of EnANPAD and SemeAD, between the years 2010 to 2018. A total of 28 articles on communication and organizational communication were identified. It is hoped that this study can contribute and encourage the exploration of the potential of this theme, thus providing the increase of research on organizational communication, especially in the EnANPAD meeting, since the results of this research indicated a low production of articles in this area.
Keywords: Organizational Communication; Communication; Organizations